2003
DOI: 10.1117/12.474862
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of InGaAsP/InP buried heterostructure DFB lasers for 10-Gbit/s operation up to 100°C

Abstract: The optimisation of a 1300nm buried heterostructure (BH) InGaAsP/InP DFB laser for uncooled directly modulated 10Gbit/s operation is described. The development process as well as the key process parameters are discussed and results are presented on an optimised structure. Bandwidths in excess of 10GHz were measured at 90C chip base temperature. Clean open eye diagrams were recorded over the full temperature range, resulting in error free transmission over 40km. To our knowledge the results represent the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The second regrowth is not selective and consists of the p-InP cladding and ternary layers. Charles et al [12] demonstrated modulation of a blocking-junction FP DFB laser of 10 Gb/s up to 100°C.…”
Section: Introductionmentioning
confidence: 99%
“…The second regrowth is not selective and consists of the p-InP cladding and ternary layers. Charles et al [12] demonstrated modulation of a blocking-junction FP DFB laser of 10 Gb/s up to 100°C.…”
Section: Introductionmentioning
confidence: 99%